2020
DOI: 10.1164/rccm.201910-1926oc
|View full text |Cite
|
Sign up to set email alerts
|

Respirable Crystalline Silica Exposure, Smoking, and Lung Cancer Subtype Risks. A Pooled Analysis of Case–Control Studies

Abstract: results interpretation, and original drafting of the work. Authors #45-48 contributed to the original conception of the project and secured project funding. Authors 7-48 participated in data acquisition and data analysis design of the project. All authors participated in critical revision of the manuscript and provided approval of the finalized submitted version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 25 publications
5
30
0
1
Order By: Relevance
“…The meta-analysis of results on DE exposure in non-smokers did not provide evidence of an independent effect of the former. This is similar to what has been detected for other lung carcinogens such as chrysotile asbestos (Klebe et al, 2019) and silica (Ge et al, 2020), that appears to entail a minimal, if any, risk in the absence of tobacco smoking, probably because of low exposure levels.…”
Section: Discussionsupporting
confidence: 85%
“…The meta-analysis of results on DE exposure in non-smokers did not provide evidence of an independent effect of the former. This is similar to what has been detected for other lung carcinogens such as chrysotile asbestos (Klebe et al, 2019) and silica (Ge et al, 2020), that appears to entail a minimal, if any, risk in the absence of tobacco smoking, probably because of low exposure levels.…”
Section: Discussionsupporting
confidence: 85%
“…Workers in agriculture, construction, mining, quarrying, and manufacturing of metal products may be exposed to high concentrations of respirable silica ( Peters et al , 2011 ; IARC, 2012 ). Respirable crystalline silica exposure is a well-documented risk factor for silicosis ( t Mannetje et al , 2002 ) and lung cancer ( IARC, 2012 ; Ge et al , 2020 ) and is associated with the occurrence of rheumatoid arthritis, systemic sclerosis, and other autoimmune rheumatic diseases ( Miller et al , 2012 ; Boudigaard et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago, smoking was considered as a risk factor for the development of silicosis in workers exposed to silica dust [ 35 ]. Even low exposure levels of respirable crystalline silica have been associated with lung cancer [ 36 ]. Moreover, several studies have shown that smoking can increase the harmful effect of exposure to silica dust [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%